Two Extremely Low Birth Weight Infants Who Survived Functional Pulmonary Atresia with Normal Intracardiac Anatomy - Shuntaro Oka; Utako Kondo; Ayumi Oshima; Shun Matsumura; Masayo Kanai; Akio Ishiguro; Yoichi Iwamoto; Hirotaka Ishido; Isaku Omori; Satoshi Masutani (Thieme Medical Publishers, Inc., 2019)
For the first time, we report about two extremely low birth weight infants who were born at 25 and 22 weeks' gestation and who survived functional pulmonary atresia (fPA) with normal intracardiac anatomy. A slow, reflected, and bimodal blood flow pattern in the pulmonary artery (both cases) and the presence of pulmonary regurgitation (1 case) were useful for diagnosing fPA. Timely use of lipo-prostaglandin E1 to maintain adequate pulmonary flow and reduce pulmonary arterial resistance and sodium bicarbonate to improve acidosis were effective treatments to attain forward flow. As optimal management is essential for the intact survival of extremely early preterm infants and the accurate diagnosis of fPA is difficult without the awareness of the disease entity, our cases underline the importance of recognizing that fPA can occur even in extremely low birth weight infants with normal intracardiac anatomy.